Interaction of the Hypothalamic Paraventricular Nucleus and Central Nucleus of the Amygdala in Naloxone Blockade of Neuropeptide Y-Induced Feeding Revealed by c-fos Expression - Pomonis, James D. (J Neurosci, 1997)
Neuropeptide Y (NPY) is a powerful inducer of food intake with a key site of action in the paraventricular nucleus (PVN) of the hypothalamus. An effective method for inhibiting the effects of NPY is pretreatment with the opioid antagonists naloxone or naltrexone. In the present study, we used immunohistochemistry for cFos as a marker of neuronal activity to map the effects of PVN-injected NPY and blockade of these effects by peripheral injection of naloxone. Injection of NPY into the PVN resulted in an increase in food intake that was blocked by peripheral administration of naloxone. PVN NPY also resulted in increased cFos immunoreactivity (cFos-IR) in the PVN independent of food intake, and although peripheral naloxone inhibited NPY-induced feeding, it did not alter cFos-IR in the PVN. cFos-IR in the central nucleus of the amygdala (CNA) increased in response to both NPY and naloxone. Furthermore, the response to NPY and naloxone was additive, suggesting that peripheral naloxone and PVN NPY activate different neuronal populations in the CNA. Three other brain regions, the nucleus of the solitary tract, the ventrolateral medulla, and the supraoptic nucleus, all showed increases in cFos-IR in this study, but these changes came only as a result of increased food intake after PVN-injected NPY. The current data suggest that the CNA is a site important for the integration of the NPY and opioid systems.